Imaging of Folate Receptor Expressing Macrophages in the Rat Groove Model of Osteoarthritis: Using a New DOTA-Folate Conjugate. (April 2018) - de Visser, Huub M.; Korthagen, Nicoline M.; Müller, Cristina; Ramakers, Ruud M.; Krijger, Gerard C.; Lafeber, Floris P. J. G.; Beekman, Freek J.; Mastbergen, Simon C.; Weinans, Harrie
Objective: To evaluate the presence and localization of folate receptor expressing macrophages in the rat groove model of osteoarthritis and determine the suitability of a new folate conjugate with albumin-binding entity (cm09) for in vivo SPECT (single-photon emission computed tomography) analysis. Design: In male Wistar rats, local cartilage damage was induced in addition to a standard ( n = 10) or high-fat diet ( n = 6). After 12 weeks, 111 In labeled folate conjugates were administered, and SPECT/CT (computed tomography) imaging was performed after 24 hours. Subsequently, osteoarthritis severity and folate receptor expression were assessed using (immuno)-histological sections. Results: In vivo SPECT/CT imaging of the new folate conjugate (cm09) was as useful as a folate conjugate without albumin-binding entity in the groove model of osteoarthritis with less renal accumulation. Induction of cartilage damage on a standard diet resulted in no effect on the amount of folate receptor expressing macrophages compared with the contralateral sham operated joints. In contrast, inducing cartilage damage in the high-fat diet group resulted in 28.4% increase of folate receptor expression as compared with the nondamaged control joints. Folate receptor expressing cells were predominantly present in the synovial lining and in subchondral bone as confirmed by immunohistochemistry. Conclusions: Folate receptor expression, and thus macrophage activation, can clearly be demonstrated in vivo, in small animal models of osteoarthritis using the new 111 In-folate conjugate with specific binding to the folate receptor. Increased macrophage activity only plays a role in the groove model of osteoarthritis when applied in a high-fat diet induced dysmetabolic condition, which is in line with the higher inflammatory state of that specific model.